Efficiency of the Administrative Appeal (The Case of Serbia) - Dobrosav MILOVANOVIĆ; Marko DAVINIĆ; Vuk CUCIĆ (Transylvanian Review of Administrative Sciences, 2012)
This paper completes the research of the administrative appeal under the Serbian law. It is preceded by two articles containing normative analyses of the general regime of the administrative appeal as prescribed in the General Administrative Proceeding Act and administrative remedies in special policy domains. The main part of the paper is an empirical research concerning the efficiency of the administrative appeal. Efficiency is understood as a precondition for preventing appellants from seeking judicial protection and thus reducing the workload of the court. The remaining part is dedicated to the efficiency of two other administrative legal remedies, as well as to the efficiency of the work of the Ombudsman. The purpose of the latter is to provide material for the consideration of possible amendments to the regime of the administrative appeal, which could enhance its efficiency.